Efektivitas Model Problem Based Learning Materi Sifat Magnet Kelas VI B SDN Sawah Besar 01 Semarang - Yuli Cahyaningrum; Duwi Nuvitalia; Bagus Ardi Saputro; Hamidah Noer (STKIP Andi Matappa Pangkep, 2023)
This study aims to describe the Problem Based Learning Learning Model on the magnetic properties of natural science subjects. This research method uses a qualitative methodology. This study uses data collection techniques, namely observation, interviews and documentation. Researchers analyzed data from research results in a qualitative description. This study obtained the results that the problem-based learning model had a positive effect on student learning activities on the magnetic properties of science subjects, the percentage results showed that after the application of the problem-based learning model as many as 25 students scored above the KKM with a total percentage of 92.5% and as many as 2 students scored below the KKM with a total percentage of 7.4%. The problem-based learning learning model is a learning model that is useful for encouraging students to learn actively and be able to solve their own problems so that the learning outcomes produced by students can be remembered continuously.Â